Cadmium induced hepatic intoxication and amelioration by grape seed extract - Adel Alkhedaide, Adel; Youssef, Gehan; El-Zoghby, Rabab; Mahmoud, Mohamed; Atwa, Shimaa (International Journal of Pharmacology and Toxicology, 2017)
Cadmium (Cd) is wide-spread toxic metal that pollutes most of the vegetables, which eaten by numerous populations all over the world. The aim of the current work is to evaluate the protective and prophylactic effects of the antioxidant materials in the grape seed extract (GSE) on the hepatic intoxication induced by cadmium chloride toxic material in male Wistar rats. Male adult Wistar rats were divided into four groups. Control group fed on balanced diet and given drinking water. Group two (control positive) given CdCl2 in the dose of 0.44 mg/kg body weight (BW) by stomach tube daily. Group three given grape seed extract GSE in the dose of (100 mg/kg BW) daily by stomach tube. Finally, the fourth group gave mixture of (GSE and CdCl2) by stomach tube in the recommended dose. Blood and liver tissues were collected for further biochemical and histopathological studies. CdCl2 significantly increased the serum levels of malondialdehyde, ALT and AST. Cadmium administration decreased levels of antioxidants (Catalase, GSH-R and GSH-Px). The liver of the control positive groups which given CdCl2 showed degenerative changes in the form of vacuolar and hydropic degeneration. Congestion was evident in the central vein and proliferation of the kupffer cells. These hepatic biochemical and degenerative changes were ameliorated by the co addition of GSE.